Performance evaluation of thermochemical energy storage system based on lithium orthosilicate and zeolite. (15th April 2019) - Takasu, Hiroki; Hoshino, Hitoshi; Tamura, Yoshiro; Kato, Yukitaka
Highlights: Lithium orthosilicate/zeolite/carbon dioxide system is proposed for use in chemical heat pump systems at around 700 °C. The maximum gravimetric mean thermal output and input rates of lithium orthosilicate were 7.2 and 1.9 kW kg −1 . The proposed thermochemical energy storage system required an amount of zeolite 2.4 times the mass of lithium orthosilicate. Abstract: High-temperature thermal energy can be produced from renewable power sources such as high-temperature gas-cooled reactors and high-temperature thermal processes, without environmental pollution. Integration of thermochemical energy storage (TcES) systems within power generation systems provides flexible options for future power generation. This study evaluates the performance of a TcES system based on Li4 SiO4 /zeolite/CO2 for thermal energy storage at ∼700 °C. Isothermal experiments with Li4 SiO4, accessed through a solid-state reaction method, revealed that carbonation and decarbonation were almost complete after 5 and 150 min, respectively. The maximum gravimetric mean thermal output and input rates were 7.2 and 1.9 kW kg −1 for Li4 SiO4 (59% porosity), respectively. Moreover, zeolite F-9 was examined as a pressure conditioning material by investigating the CO2 desorption profile at various CO2 pressures, and ∼15 wt% CO2 could be controlled. The zeolite showed good cycling durability and temperature responsiveness for four repeated cycles. Hence, the TcES system based on Li4 SiO4 and the zeolite could be used for thermal energy storage at about 700 °C, and only temperature control was required to switch between the output and input modes. The amount of zeolite required by the proposed TcES system was 2.4 times (by weight) greater than that of Li4 SiO4 .